Optical and electrical properties of manganese doped-alkali metaphosphate glasses. (2020) - Jerroudi, M.; Bih, L.; Haily, E.; Yousfi, S.; Bejjit, L.; Haddad, M.; Manoun, B.; Lazor, P.
Abstract: Phosphate glasses are of large interest for a variety of technological applications due to their several unique properties. In this work we investigate structural, optical and electrical properties of some alkali metaphosphate glasses doped with manganese oxide inside the system (50-x/2) K2 O-xMnO2 -(50-x/2) P2 O5 with (0 ≤ x ≤ 30%mol). The glassy samples have been prepared using a melt-quench process. The obtained glasses are colored and the valence of manganese is composition dependence. The local structure of Mn 2+ in the glasses is evaluated by EPR spectroscopy. The optical absorption spectra have been used to evaluate the values of the optical band gap (Eg ) and Urbach energy (ΔE). The variation of these optical parameters as a function of composition is investigated. The presence of Mn 3+ in the glasses is established by the optical absorption and this ion is associated with the absorption band at 520–530 nm. dc conductivity of the glasses is studied and it is found that it is thermally activated and followed an Arrhenius behavior.